North of the great divide - Witney, William, 1915-2002; Rogers, Roy, 1911-1998; Republic Pictures Corporation; Cinetel Films (Los Angeles, CA : Republic Pictures Corporation, 1950)
The women and children of the Oseka Indians are starving to death during a bitter dispute with a conniving cannery owner. A U.S. Indian Affairs Agent is called in to settle the feud.
Roy Rogers, Penny Edwards, Gordon Jones, Trigger, Foy Willing and the Riders of the Purple Sage.
Director of photography, Jack Marta; editor, Tony Martinelli; music, R. Dale Butts.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 14, 2015)
Keywords: Royal Canadian Mounted Police -- Drama; Indians of North America -- Northwest, Canadian -- Drama; Indians of North America -- Northwest, Pacific -- Drama; Pacific salmon fishing -- Northwest, Pacific -- Drama; Western films; Feature films; Internet videos; Streaming video